ARTIFICIAL INTELLIGENCE AND BUSINESS ETHICS IN MODERN SOCIETY INFERRED FROM THE TEACHINGS OF HOLY PROPHET PBUH - Dr Wajid Ali; Prof. Dr. Matloob Ahmad*; Hafiz Muhammad Gulzar Ramzan (Journal of Religion and Society, 2025)
Artificial Intelligence is a field of science concerned with building computers and machines that can reason learn out in such way that would normally require human intelligence or that involves data whose scale exceed that human can analyze. Artificial Intelligence eliminate human errors during tasks and deliver more precise and dependable results. Artificial Intelligence boosts productivity by optimizing processes and reducing time and resources. Artificial Intelligence is dire need for present age because it is the age of science. Artificial Intelligence process and analyze large volume of data quickly gave personalization solutions based on customer data. Healthcare and other element which are improving day by day through artificial intelligence. Artificial Intelligence offer numerous benefits including task automation improve efficiency reduce human mistakes and enhance customer satisfaction. Business Ethics can play very important role to improve economy. Business Ethics refer to implementing appropriate business policies and practices with regard to arguably controversial subjects. In market business Ethics including accountability, care, respect, honesty, healthy competition, loyality, transparency and respect for value of law The prophet Muhammad PBUH encouraged businessmen to give in charity and help those in need .He said, O Marchants! There are five things which no one associated with trade should do tell lies, break promises,conceal facts ,refuse reasonable requests and stop reasonable credit.The foundation of business ethics according to Holy Prophet Muhammad PBUH said the buyer and the seller have the option of cancelling or conforming the bargain useless they separate and if they spoke truth and made clear the deficits of goods then they would be blessed in their bargain. In Modern Society it is need fair pricing and avoiding expolition fulfill commitments.The Holy Prophet Muhammad PBUH used to give people their rights and urge others to do like ise.The motive of Muslim business person to give benefits to others.The Holy Prophet Muhammad PBUH forbade blocking a trading carvan .The person of Muhammad PBUH before becoming a Prophet and Apostal was known as the person with noble character as businessman .The impact of applying business ethics to the Prophetic teachings do not hoard goods to obtain high profit.The principle of volunteering or mutual liking needs to be applied in business ethics. Keywords: Artificial Intelligence, Business Ethics, Modern Society Boosts Productivity Healthcare, Customer Satisfaction, Honesty, Expolition, Mutual Understanding